2019
DOI: 10.1002/jcb.29477
|View full text |Cite
|
Sign up to set email alerts
|

SNHG16 as the miRNA let‐7b‐5p sponge facilitates the G2/M and epithelial‐mesenchymal transition by regulating CDC25B and HMGA2 expression in hepatocellular carcinoma

Abstract: Long noncoding RNAs (lncRNAs) play crucial roles in hepatocellular carcinoma (HCC). However, the underlying molecular mechanisms of small nucleolar RNA host gene 16 (SNHG16) for regulating the cell cycle and epithelial to mesenchymal transition (EMT) remain elusive. In this study, SNHG16 expression profiles of HCC tissues or cell lines were compared with those of normal tissues or hepatocyte cell line. The effect of SNHG16 knockdown in HCC cell lines was investigated by using in vitro loss-of-function experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…Certainly, we cannot rule out other mechanisms are involved in the regulation of HMGA2 expression in HCC. In fact, several long noncoding RNAs (lncRNAs), such as HULC, LSINCT5, LINC00473, SNHG16 and EGOT, have been found to promote HMGA2 expression in HCC [11,[34][35][36][37]. In addition, a series of microRNAs (miRs or miRNAs)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, we cannot rule out other mechanisms are involved in the regulation of HMGA2 expression in HCC. In fact, several long noncoding RNAs (lncRNAs), such as HULC, LSINCT5, LINC00473, SNHG16 and EGOT, have been found to promote HMGA2 expression in HCC [11,[34][35][36][37]. In addition, a series of microRNAs (miRs or miRNAs)…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that HMGA2 is highly expressed in most malignant tumors, and its expression level is closely related to the degree of malignancy and metastasis, including breast, melanoma, colorectal and bladder cancer [8,9]. More important, accumulating evidence have shown that HMGA2 is highly expressed in hepatocellular carcinoma, and the elevated HMGA2 predicts high incidence of metastasis and poor patient survival in hepatocellular carcinoma [10,11]. For example, overexpression of HMGA2 is an important contributor to the invasion of hepatocellular carcinoma cells, while HMGA2 knockdown impaired the migratory capacity of tumor cells in hepatocellular carcinoma [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…SNHG16 contributes to chemoresistance in hepatocellular carcinoma. It was shown that siRNA knockdown of SNHG16 reverses sorafenib resistance in Hep3B and HepG2 cell lines [45], and sh-SNHG16 knockdown increases HuH7 and Hep3B cell sensitivities to cisplatin [47], but the underlying mechanisms were not clarified by these two studies. However, another study reported that upregulation of SNHG16 inhibits 5-fluorouracil (5-FU) chemoresistance in Hep3B and HuH7 cells [44], which contrasts the two reports mentioned above.…”
Section: Snhg16 In Chemotherapeutic Resistancementioning
confidence: 99%
“…In addition, there are some molecules reported to be mediated by SNHG16, including Stearoyl-CoA Acute Lymphoblastic Leukemia MOLT3 BALB/c nude mice promote [22] Cervical cancer HeLa BALB/c nude mice promote [29] Colorectal cancer LoVo BALB/c nude mice promote [30] Diffuse large B-cell lymphoma OCI-LY7 NOD/SCID mice promote [33] Esophageal squamous cell carcinoma kyse-70 BALB/c nude mice promote [35] Gastric cancer MGC-803 BALB/c nude mice promote [38] Hepatocellular carcinoma HuH7 athymic nude mice inhibit [44] HuH7 BALB/c nude mice promote [47] HepG2 BALB/c nude mice promote [48] HepG2 athymic nude mice promote [49] Hep-3B BALB/c nude mice promote [50] Neuroblastoma SK-N-SH BALB/c nude mice promote [51] Non small cell lung cancer A549 BALB/c nude mice promote [53,54] Oral squamous cell carcinoma TSCCA BALB/c nude mice promote [55] Pancreatic cancer AsPC-1 BALB/c nude mice promote [61] Retinoblastoma Y79 BALB/c nude mice promote [63] Desaturase (SCD) [31], p-AKT and matrix metallopeptidase 9 (MMP9) [60], Dickkopf-related protein 3 (DKK3) [39], and Wnt/β-catenin [36], but the underlying regulate mechanisms are not well uncovered. Furthermore, whether SNHG16 has other regulatory functions still needs further investigation.…”
Section: Snhg16 Regulates Various Genesmentioning
confidence: 99%
See 1 more Smart Citation